2015
DOI: 10.1111/tan.12668
|View full text |Cite
|
Sign up to set email alerts
|

Study of association of CTLA4 gene variants to non‐anterior uveitis

Abstract: This study was undertaken to investigate the possible genetic association of functional CTLA4 polymorphisms with susceptibility to non-anterior uveitis. Four hundred and seventeen patients with endogenous non-anterior uveitis and 1517 healthy controls of Spanish Caucasian origin were genotyped for the CTLA4 polymorphisms rs733618, rs5742909 and rs231775, using predesigned TaqMan(©) allele discrimination assays. PLINK software was used for the statistical analyses. No significant associations between the CTLA4 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 25 publications
0
2
1
Order By: Relevance
“…[ 23 ] While, rs733618 SNP had no significant association with nonanterior uveitis. [ 17 ] However, in this study we found that heterozygote and homozygote of rs733618 T allele were mildly associated with decreased susceptibility for RSA. At the same time, no significant association has been discovered between rs733618 alleles and RSA susceptibility.…”
Section: Discussioncontrasting
confidence: 61%
See 1 more Smart Citation
“…[ 23 ] While, rs733618 SNP had no significant association with nonanterior uveitis. [ 17 ] However, in this study we found that heterozygote and homozygote of rs733618 T allele were mildly associated with decreased susceptibility for RSA. At the same time, no significant association has been discovered between rs733618 alleles and RSA susceptibility.…”
Section: Discussioncontrasting
confidence: 61%
“…All of these SNPs were widely explored in different diseases. [ 17 19 ] However, the genetic association of these SNPs with RSA occurrence were rarely reported in Chinese Han population.…”
Section: Introductionmentioning
confidence: 99%
“…Among these studies, one had depicted other PTPN22 polymorphisms with VKH disease, and another six did not contain enough genotypic data. Finally, 20 published records with 5,320 cases and 8,839 controls were included in our meta-analysis [13,16,[25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42].…”
Section: Literature Searchmentioning
confidence: 99%